Little raindrop - Guzman, Gloria Villaraza; Manto, Fidelito (Quezon City Adarna House, 2003)
All the uses of water are illustrated in the story of Little Raindrop and his siblings. Through their story we realize the value of water in our lives.
A story of a little raindrop who learns about his role in the world.
Keywords: Raindrops -- Juvenile literature; Water -- Juvenile literature